2015
DOI: 10.1039/c5gc01336d
|View full text |Cite
|
Sign up to set email alerts
|

A choline chloride/DMSO solvent for the direct synthesis of diformylfuran from carbohydrates in the presence of heteropolyacids

Abstract: Here we report the one pot conversion of fructose to DFF in the presence of a mixture of choline chloride (ChCl) and DMSO as a solvent and Mo-Keggin heteropolyacids.Here we demonstrate that choline chloride has a beneficial effect on the direct conversion of fructose and inulin to DFF in the presence of Mo-V containing Keggin heteropolyacid. ChCl have two beneficial effects : 1) the enhancement of the conversion of fructose to HMF and 2) a higher conversion of HMF to DFF. A yield to DFF of 84% was obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…To date, direct synthesis of DFF from fructose has been achieved by using POMs as catalysts.L iu et al reportedt hat 58 % yield of DFF was obtained directly from fructoseu pon using H 3 PMo 12 O 40 with 100 %c onversion under reactionc onditions of 160 8C, 6h,i nD MSO. [29] Recently,L ee and co-workers achieved H 3 PMo 12 O 40 encapsulated on MIL-101 (PMA-MIL-101) to catalyze fructose conversion into DFF in DMSO with 75.1 %y ield of DFF at 81 %f ructose conversion at 110 8Cf or 1h. Then, Cs 3 HPMo 11 VO 40 was adopted in the one-step dehydration-oxidation of fructoset oD FF with 60 %y ield at > 99 %c onversion under reaction conditions of 120 8C, 8h,i nD MSO.…”
Section: Introductionmentioning
confidence: 99%
“…To date, direct synthesis of DFF from fructose has been achieved by using POMs as catalysts.L iu et al reportedt hat 58 % yield of DFF was obtained directly from fructoseu pon using H 3 PMo 12 O 40 with 100 %c onversion under reactionc onditions of 160 8C, 6h,i nD MSO. [29] Recently,L ee and co-workers achieved H 3 PMo 12 O 40 encapsulated on MIL-101 (PMA-MIL-101) to catalyze fructose conversion into DFF in DMSO with 75.1 %y ield of DFF at 81 %f ructose conversion at 110 8Cf or 1h. Then, Cs 3 HPMo 11 VO 40 was adopted in the one-step dehydration-oxidation of fructoset oD FF with 60 %y ield at > 99 %c onversion under reaction conditions of 120 8C, 8h,i nD MSO.…”
Section: Introductionmentioning
confidence: 99%
“…This observation offers interesting perspectives as Please do not adjust margins Please do not adjust margins DMSO is typically considered to be a green solvent. [42][43][44] These results revealed that the role of the solvent is complex and cannot be simply described in terms of polar vs. nonpolar or protic vs. aprotic properties. At first glance, one could conclude that the polarity of the solvent would explain Mlac vs. ttMA reaction pathways, but if that were the case Scheme 6.…”
Section: Isomerization To Ttma In Polar Aprotic Solventsmentioning
confidence: 99%
“…The IR spectrum of the catalyst showed that the Keggin structure was maintained. Using a Mo-Keggin heteropolyacid catalyst, Ghezali et al studied the direct conversion of fructose to diformylfuran (DFF) [29]. During this reaction, the acid and the oxidative sites of the catalysts were used to dehydrate fructose to HMF and to oxidize HMF to DFF.…”
Section: Synthesis Of Furanic Derivatives In the Presence Of A Des Comentioning
confidence: 99%